(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The introduction of the human rights in the Constitutions, that is the main characteristicof the Constitutional states, has given an important role to ConstitutionalCourts because they are responsible for protecting and interpreting those rights. Thisrole assigned to judges has been discussed because it means a restriction to the decisionsthat can be adopted by a political majority. In this paper, the characteristics ofthe tension between democracy and constitutionalism will be studied and it will beargued that judicial power can be a guarantee of democracy if we understand its roleas an interpretative role of the contents of the Constitution.